2015
DOI: 10.1007/s10750-015-2428-5
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity in wild marine fishes associated with fish-cage aquaculture

Abstract: Two opportunistic fish species associated with fish farms, bogue (Boops boops) and salema (Sarpa salpa), were studied to infer whether changes in their feeding habits may cause a phenotypic response in body and otolith shape. Specimens were collected close to aquaculture cage sites, called 'wildfarmed fish', and from control sites far away from these areas, called 'wild fish'. The fish body shapes were examined with geometric morphometric analysis using 21 landmarks. The otolith contours were analysed using wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 114 publications
(124 reference statements)
0
19
0
Order By: Relevance
“…Fish in farm sites were, on average, smaller than those in reference areas, which was reflected in lower growth rates, as detected by otolith measurements in salema (S. salpa). Abaad et al (2016) also found that otolith size varied for salema between seabream/ seabass farm cage sites and natural sites on Gran Canaria (Canary Islands) but that fish size-corrected otoliths were larger in fish close to farms than in those from reference sites; the size of bogue otoliths did not differ between treatment areas.…”
Section: Growth and Reproductive Successmentioning
confidence: 85%
See 1 more Smart Citation
“…Fish in farm sites were, on average, smaller than those in reference areas, which was reflected in lower growth rates, as detected by otolith measurements in salema (S. salpa). Abaad et al (2016) also found that otolith size varied for salema between seabream/ seabass farm cage sites and natural sites on Gran Canaria (Canary Islands) but that fish size-corrected otoliths were larger in fish close to farms than in those from reference sites; the size of bogue otoliths did not differ between treatment areas.…”
Section: Growth and Reproductive Successmentioning
confidence: 85%
“…Abaad et al . () also found that otolith size varied for salema between seabream/seabass farm cage sites and natural sites on Gran Canaria (Canary Islands) but that fish size‐corrected otoliths were larger in fish close to farms than in those from reference sites; the size of bogue otoliths did not differ between treatment areas.…”
Section: Interactions Between Finfish Farms and Wild Populationsmentioning
confidence: 88%
“…In these species, this plasticity apparently depends on food quality (i.e. food rich in fatty acids versus food with lower fatty acid concentrations; Abaad et al, ). Bogue associated with fish farms (and hence a supply of food rich in fatty acids) did not show significant differences in the mass or 2D contour of saccular otoliths compared to individuals living far from such farms.…”
Section: Evolution Of Teleost Otolithsmentioning
confidence: 99%
“…This also applies to taxon-specific differences in otolith morphology (e.g. Vignon & Morat, 2010;Abaad et al, 2016). Seasonal plasticity was observed in the number of ciliary bundles on the macula sacculi and in hearing abilities of female plainfin midshipman [Porichthys notatus (Batrachoididae) (Sisneros et al, 2004;Coffin et al, 2012a)].…”
Section: (2) Ecomorphology and Phenotypic Plasticitymentioning
confidence: 99%
“…Nevertheless, body shape is also used because it is a multifunctional and single factor related to aspects of behavioural ecology, such as the mode of feeding, predator evasion or courtship displays (Lavin and McPhail 1985;Loy et al 2000;Walker 2010). In addition, body shape may also be influenced by anthropogenic activities, such as aquaculture or fishing pressure (Alós et al 2014;Abaad et al 2016).…”
Section: Introductionmentioning
confidence: 99%